Nucleotide sequence of the guaB locus encoding IMP dehydrogenase of Escherichia coli K12. - Tiedeman, A A (1985)
IMP dehydrogenase, the product of the guaB locus in Escherichia coli K12, catalyzes the synthesis of XMP by the NAD+ dependent oxidation of IMP. The guaB locus has been subcloned from the Clarke and Carbon plasmid pLC34-10. The sequence of the guaB structural gene and surrounding DNA was determined by the dideoxy chain termination method of Sanger. The 1.533 kb guaB gene encodes an IMP dehydrogenase subunit of molecular weight 54,512. S1 nuclease mapping placed the site of guaBA mRNA initiation approximately 188 bp from the start of the guaB structural gene. The -10 and -35 regions that define the guaBA promoter were located upstream of the start of the guaBA transcription initiation site. The control region of approximately 188 bp does not show any obvious potential for secondary structure. A secondary lambda att site has been identified 42 bp distal to the guaB start codon.